Nationalism and After - Carr, E.H. author. aut Link
LVII, 59 p.
Keywords: “In this timely reissue of Carr's classic work on nationalism, Michael Cox brilliantly unravels Carr's complex views on one of the most contentious issues of the last two centuries. Demonstrating striking command of both primary and secondary materials, Cox demonstrates how a figure so critical of liberal projects for cosmopolitan governance could support an international order that superseded both nationalism and the nation-state. It is a fascinating story, and Cox tells it with great dexterity and élan. As the world's borders harden once again, this book makes for essential reading.” –Professor George Lawson, Australian National University. Author, Anatomies of Revolution “In his brilliantly written essay, Professor Cox does a masterful job of taking you from Carr's experiences as a Foreign Office official dealing directly with the challenges of nationalism in post-World War I Europe, all the way up through the interwar crisis, the war years and on to the Cold War, interweaving Carr’s study of nationalism with his other abiding interests in IR and the USSR…hugely informative and illuminating.” –Professor William Wohlforth, Dartmouth College, USA. Author, America Abroad: The United States’ Global Role in the 21st Century Published in 1945, Nationalism and After was a best-selling classic in its own time which sparked intense debate when it first appeared and has continued to do so ever since. Authored in a moment of hope, E.H. Carr’s uncompromising critique of nationalism and plea for a more rational international order remains as relevant today as it did when it was first written. As the world is once again confronted by a rising tide of nationalism, Nationalism and After remains a beacon of hope in an era where reasoned critical analysis has never been more urgently required. It is here reissued in full with a new, definitive introduction by leading Carr scholar, Michael Cox. E.H. Carr (1892-1982) was educated in Cambridge, joined the Foreign Office in 1916 before going on in 1936 to become Woodrow Wilson Professor in the Department of International Politics at the University College of Wales, Aberystwyth. From 1941 to 1946 he was Assistant Editor at The Times. Michael Cox is Professor Emeritus of International Relations at the London School of Economics, UK, and Founding Director and Director of LSE IDEAS, the no. 1 university-affiliated Think Tank in the world. .